1996
DOI: 10.1002/(sici)1097-4628(19961205)62:10<1709::aid-app22>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-property relationships in ABS/PET blends. II. Influence of processing conditions on structure and properties

Abstract: SYNOPSISThe effect of processing temperature on the low-speed tensile and high-speed impact properties of novel ABS/PET blends was investigated. In agreement with the conclusions from related studies of ABS/PC blends, it appears that catalytic impurities in the ABS accentuate the propensity of PET for chain scission. Due to the cocontinuous structure of the blend, the hydrolytic or thermomechanical degradation of the PET results in a dramatic loss in mechanical properties which can be explained by the entangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…To combine the chemical polarity, crystallinity, and toughness, PET/ABS blends can be considered as a scientific challenge. These blends are also commercially significant, especially when they are formed from W‐PET and can replace the expensive polymer blends in industrial applications; there are only a few reports on this material in the open literature [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…To combine the chemical polarity, crystallinity, and toughness, PET/ABS blends can be considered as a scientific challenge. These blends are also commercially significant, especially when they are formed from W‐PET and can replace the expensive polymer blends in industrial applications; there are only a few reports on this material in the open literature [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…A simultaneous increase of tensile strength and toughness in ABS/PET blends was achieved by Cook and coworkers, and this was ascribed as due to a considerable plastic deformation in both domains 9. The effect of processing temperature on the mechanical properties as well as the phase morphology was also investigated, and it was concluded that the degradation of PET would result in a dramatic loss in mechanical properties and change in phase morphology 10…”
Section: Introductionmentioning
confidence: 93%
“…Cool et al [1,2] previously observed four domains in noncompatibilized ABS/PET blends and also noticed that the properties of the blends depended on processing conditions resulting from degradation of the PET. Paul et al [3] carried out a study on the blends of ABS/recycled PET compatibilized by styrene maleic anhydride (SMA).…”
Section: Introductionmentioning
confidence: 96%